Comparative analysis of immune infiltrates in head and neck cancers across anatomical sites - Muijlwijk, Tara; Nijenhuis, Dennis N L M; Ganzevles, Sonja H; Brink, Arjen; Ke, Changlin; Fass, Joseph N; Rajamanickam, Venkatesh; Leemans, C René; Koguchi, Yoshinobu; Fox, Bernard A; Poell, Jos B; Brakenhoff, Ruud H; et al. (Journal for immunotherapy of cancer, 2024)
BackgroundThe response rate to immune checkpoint inhibitors targeting programmed cell death 1 (PD-1) receptor is 13%–18% for patients with recurrent or metastatic head and neck squamous cell carcinoma (HNSCC). Detailed understanding of the tumor immune microenvironment (TIME) is crucial in order to explain and improve this response rate. HNSCCs arise at various anatomical locations including the oral cavity, hypopharynx, larynx and oropharynx. Studies directly comparing immune infiltration between anatomical sites are scarce. Since the distinct locations could drive deviating microenvironments, we questioned whether the immune composition varies across these HNSCC sites.MethodsHere, we characterized the TIME of 76 fresh tumor specimens using flow cytometry and performed single-cell RNA-sequencing on nine head and neck tumor samples.ResultsWe found major differences in the composition of the TIME between patients. When comparing anatomical sites: tumors originating from the oral cavity had higher T cell infiltrates than tumors from other anatomical sites. The percentage of tumor-infiltrating T-lymphocytes positive for the immune checkpoint PD-1 varied considerably between patients, with the highest fraction of PD-1+ T cells found in larynx squamous cell carcinomas (SCCs). While we had hypothesized that the anatomical sites of tumor origin would drive sample clustering, our data showed that the type of TIME was more dominant and was particularly driven by the fraction of T cells positive for PD-1. Moreover, a high proportion of PD-1+ CD8+ T cells associated with an improved overall survival. Using single-cell RNA-sequencing, we observed that PD-1 expression was highest in the CD8-ENTPD1 tissue resident memory T cell/exhausted T cell and CD4-CXCL13 type 1 T helper cell clusters.ConclusionsWe found that oral cavity SCCs had the highest frequencies of T cells. We also observed considerable interpatient heterogeneity for PD-1 on T cells, with noticeably higher frequencies of PD-1+ CD4+ T helper cells in larynx SCCs. Within the entire cohort, a higher fraction of CD8+ T cells positive for PD-1 was linked to improved overall survival. Whether the fraction of PD-1+ T cells within the TIME enables immune checkpoint inhibitor response prediction for patients with head and neck cancer remains to be determined.